Ethnotourism In The Bukhara Oasis: Opportunities, Achievements and Problems - Ulugbekovich, Bobojonov (Buletin Antropologi Indonesia, 2025)
The Bukhara oasis’ geographic location, distinctive natural environment, rich historical and ethnographic legacy, and potential for modern tourism are all thoroughly examined in this article. This historic oasis, which is centred on the Zarafshan River, is notable for its multiethnic makeup, national cuisine, craftsmanship, and architectural traditions. Through the harmony of Bukhara’s ancient residential architecture, verandas, tandir kitchens, and guest rooms with art and nature, the author examines the aesthetic preferences and worldview of the local populace. Important details regarding the historical neighbourhoods of different ethnic groups, including Turkmens, Iranians, and Jews, as well as their cultural and religious landmarks, are also included in the article. The article illustrates how Bukhara used to look based on old photos from the late 19th and early 20th centuries. Today, national customs, folk applied arts, and culinary culture are being actively promoted by ethnotourism destinations like Shirin, Sheykhon, Qorgon, and Borontepa. The author lists the issues impeding ethnotourism’s growth and makes recommendations for how to address them. This article portrays Bukhara as an outdoor ethnographic museum that is crucial to the growth of global travel.